(untitled) (The Pakistan Development Review, 2006)
Pakistan Institute of Development Economics (PIDE) and Lahore University of Management Sciences (LUMS) jointly organised a seminar to discuss issues pertaining to “Law and Economics” and “Public Choice”, and their relevance for the future growth prospects of Pakistan. Dr Nadeem Ul Haque, Director, PIDE, and Osama Siddique, Head, Department of Law and Policy, LUMS, highlighted the main issues in their welcome remarks, and raised some basic questions: Can Pakistan achieve its growth target of 10 percent under the current legal framework? Does our law support free enterprise? Can the dual target of growth and free enterprise development be realised under our existing constitution? Do we need to review and make amendments to it? The high point of the meeting was the coming together of eminent lawyers and economists (and social scientists) on one forum and approaching the problem from a multidisciplinary point of view. A healthy debate followed in which some of our distinguished participants even turned the debate upside down by posing question as to what form of economic system are we hoping for. The main issues that emerged out of this deliberation are summarised below.